Examining The Impact of Employees’ Wellbeing on Performance: A Study of International Non-Governmental Organizations KRI - Ali, Mehabad Sadi; Hamakareem , Dastan Mohammed (Zanco Journal of Human Sciences, 2024)
Employee wellbeing has emerged as a compelling area of research in the fields of Human Resource Management (HRM) and organizational behavior. This study focuses on investigating the impact of employee wellbeing on job performance within International Non-Governmental Organizations (INGOs) operating in the Kurdistan Region of Iraq (KRI). The research hypothesis positsthose higher levels of employee wellbeing positively influence job performance. The primary aim is to explore the correlation between employee wellbeing and job performance, employing a quantitative approach through an online survey for data collection. A total of 181 individuals employed in INGOs participated in the study. The analysis revealed a robust positive correlation between employee wellbeing and job performance, suggesting that INGOs must exert significant efforts to enhance employee wellbeing. Furthermore, several recommendations are offered for academics, INGOs, and specifically human resource departments. Additionally, recommendations for future studies in this area are presented.